AKUNTANSI BARANG TEGAHAN: PENGAKUAN, PENGUKURAN, DAN PELAPORANNYA - Ali Tafriji Biswan; Retno Dwi Larasati (SUBSTANSI, 2021)
Customs and excise standing goods are unique items in the management of BMN, their designation and valuation must be determined so that the BMN accounting process can be carried out. This study aims to analyze the accounting practices of State-Owned Goods (BMN) originating from customs clearance and based on government accounting standards related to inventory (PSAP) No. 5). PSAP does not regulate specific goods related to the stand. This qualitative study uses a field case study model at the Directorate General of Customs and Excise (DJBC). The results of the study show that in general, the accounting practices of reclaimed goods meet government accounting standards, but it is necessary to classify earlier the status of all BMNs that have been reclaimed so that they can be included in the SIMAK BMN application, affirmation of the BMN designation by all DGCE work units, and the measurement and presentation of the entire BMN. It is necessary to have a policy regarding uniformity in the allocation of BMN for bulk goods in each work unit and synergies with other units in terms of these assets.